Development and validation of chemometric-assisted spectrophotometric method for the simultaneous estimation of aceclofenac, paracetamol, and chlorzoxazone with impurities - Rajshree Gunjal; Arti Gajbhar; Vijaya Vichare; Abhijeet Sutar; Minal Deshmukh; Vishnu Choudhari (Biomedical and Biotechnology Research Journal, 2022)
Background: Analysis of tertiary mixtures of analytes along with their impurities with simple and cost effective manner is always of interest. Utility of chemometric techniques are growing in pharmaceuticals, it improve speediness in the analysis and also provide analytical solutions with reduce the number of steps in the analytical method. In this study UV-Visible spectrophotometry coupled with principle component regression (PCR) and partial least square (PLS) multivariate methods was applied for estimation of three drugs in their formulation. Method: The calibration and validation sets were prepared in linear concentration range of three drugs and major impurities of paracetamol and aceclofenac. The series of sets were prepared using multilevel multifactorial design. Leave- One-Out (LOO) cross validation technique was employed to get essential number of Latent variables (LVs) that provides the greatest predictive ability. The developed method was studied for qualitative and quantitative analysis of titled drugs and validated as per regulatory guidelines. Results: The results showed the values of coefficient of determination (R2) for all drugs and impurities was higher than 0.99 indicating high acceptability. The obtained RMSE values were relatively low. Coefficient of determination and RMSE values indicate good accuracy and precision, respectively. Conclusion: Proposed method was successfully used for analysis of aceclofenac, paracetamol and chlorzoxazone in tablet dosage form and major impurities of aceclofenac, paracetamol in bulk.